RISK FACTORS ASSOCIATED WITH DIABETES AND HYPERTENSION IN ELDERLY INDIVIDUALS: AN INTEGRATIVE REVIEW - Guimarães, Tânia Maria Rocha; Silva, Robson de Araújo; Tomaz, Denis de Carvalho; Henrique, Juliana de Souza; Almeida, Émily Rosane de Melo; Carneiro, Mariane Gomes (Editora Impacto Científico, 2025)
Objective: To identify the main risk factors associated with the development of diabetes mellitus and systemic arterial hypertension in the elderly. Methods: An integrative review study was conducted through an electronic search in the MedLine, PubMed, and SciELO databases. The Health Sciences Descriptors used were: risk factor, diabetes mellitus, hypertension, and aged, combined by the Boolean operator "AND." Articles published between 2023 and 2025 were selected. No language restrictions were established to maximize search capacity. Data collection was carried out in July and August 2025. Results: This review consisted of nine studies. The analysis of the studies resulted in three thematic units: 1. Demographic factors; 2. Dietary consumption patterns, obesity, and sedentary lifestyle; 3. Comorbidities, treatment adherence, and polypharmacy. Final considerations: The main risk factors associated with diabetes mellitus and hypertension in the elderly were: advanced age, gender (female), low socioeconomic status, high carbohydrate and animal fat intake, overweight/obesity, metabolic complications (high cholesterol, hypertriglyceridemic waist-to-height ratio), sedentary lifestyle, polypharmacy, and low treatment adherence. This information can support public policies, programs, and goals to reduce hypertension and diabetes, especially in the most vulnerable groups. DOI: https://doi.org/10.56238/edimpacto2025.060-019